2017
DOI: 10.1111/jph.12656
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression and periplasmic secretion of an antifungal Bacillus amyloliquefaciensBLB369 endo‐β‐1,3‐1,4‐glucanase in Escherichia coli

Abstract: The endo-β-1,3-1,4-glucanases are glycoside hydrolases involved in the enzymatic depolymerization of 1,3-1,4 β-glucans and showed an antifungal activity against some fungi. Bacillus amyloliquefaciens BLB369 has a high antagonistic activity against phytopathogenic fungi. Its glu369 full-coding sequence of the endo-β-1,3-1,4-glucanase gene (732 bp) was sequenced, cloned and successfully expressed in Escherichia coli Top10. The encoded protein (243 amino acids) has a calculated molecular mass of 27.3 kDa. To simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…A study by Jin et al ( 2011 ) showed that β-1,3–1,4-glucanase from endophytic Bacillus subtilis could be a desirable vital agent against microbial pathogens with higher efficiency and lower toxicity, they proved that the bacterial enzyme had a broad antimicrobial spectrum against fungal and bacterial strains. Antifungal effect of β-1,3–1,4-glucanase was also reported by Dewi et al ( 2016 ), Xu et al ( 2016 ), Zalila-Kolsi et al ( 2018 ) and Yuan et al ( 2020 ).…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…A study by Jin et al ( 2011 ) showed that β-1,3–1,4-glucanase from endophytic Bacillus subtilis could be a desirable vital agent against microbial pathogens with higher efficiency and lower toxicity, they proved that the bacterial enzyme had a broad antimicrobial spectrum against fungal and bacterial strains. Antifungal effect of β-1,3–1,4-glucanase was also reported by Dewi et al ( 2016 ), Xu et al ( 2016 ), Zalila-Kolsi et al ( 2018 ) and Yuan et al ( 2020 ).…”
Section: Introductionsupporting
confidence: 69%
“…(human pathogenic), Yuan et al ( 2020 ) also reported the antifungal effect of β-1,3–1,4-glucanase against Canidia albicans (human pathogenic yeast). The enzyme also showed a weak antifungal effect against the phytopathogenic Aspergillus niger , the antifungal activity of the enzyme against phytopathogenic fungi was previously reported against Curvularia affinis and Colletotrichum gloeosporioides (Dewi et al 2016 ), Cryphonectria parasitica , Cylindrocladium quinqueseptatumI, Helicobasidium purpureum (Xu et al 2016 ), and Alternaria alternata (Zalila‐Kolsi et al 2018 ). Juice clarification by semi-purified β-1,3–1,4-glucanase enzyme showed variation in clarification yields of different juices at their different pH values.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The resultant OmpA-His-Glu369 fusion protein incorporated the OmpA signal sequence for E. coli periplasmic targeting, followed by a 6xHistidine tag for purification purposes. Owing to these beneficial attributes, endo-β-1,3-1,4-glucanase holds significant potential for various biotechnological applications [ 35 ] ( Figure 3 ).…”
Section: Gene Expression Using Bacillus Amyloliquefaciensmentioning
confidence: 99%
“…Furthermore, B. amyloliquefaciens has applications in biotechnology, where it is employed as a host to produce heterologous proteins and as a source of valuable biomolecules. The diverse applications of B. amyloliquefaciens highlight its importance in advancing sustainable and eco-friendly solutions across multiple sectors [ 5 , 8 , 11 , 17 , 21 , 24 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: The Importance and Applications Of The Bacillus Am...mentioning
confidence: 99%